Dynamic analysis of lunar lander during soft landing using explicit finite element method. (July 2018) - Zheng, Guang; Nie, Hong; Chen, Jinbao; Chen, Chuanzhi; Lee, Heow Pueh
Abstract: In this paper, the soft-landing analysis of a lunar lander spacecraft under three loading case was carried out in ABAQUS, using the Explicit Finite Element method. To ensure the simulation result's accuracy and reliability, the energy and mass balance criteria of the model was presented along with the theory and calculation method, and the results were benchmarked with other software (LS-DYNA) to get a validated model. The results from three loading case showed that the energy and mass of the models were conserved during soft landing, which satisfies the energy and mass balance criteria. The overloading response, structure steady state, and the crushing stroke of this lunar lander all met the design requirements of the lunar lander. The buffer energy-absorbing properties in this model have a good energy-absorbing capability, in which up to 84% of the initial energy could be dissipated. The design parameters of the model could guide the design of future manned landers or larger lunar landers. Highlights: Soft-landing analysis of a lunar lander is carried out using Explicit FE-method. Energy and mass balance criteria are presented to ensure the simulation accuracy. Benchmark analysis of software is carried out for validating the numerical model. Four critical responses of this lunar lander during landing are analyzed. Three cases results show that the lander design satisfies the landing requirement.